Case report: Hybrid approach in the management of a complete persistent sciatic artery aneurysm. (2020) - Yang, Andrew; Hashmi, Ammar; Androsov, Anton; Salzler, Gregory; Ryer, Evan
Highlights: Persistent sciatic arteries are an uncommon embryological vascular phenomenon. Persistent sciatic arteries are usually asymptomatic but may become aneurysmal. Aneurysmal degeneration can cause neuropathy and embolic complications. Both open surgical and endovascular approaches may be suitable treatment options. Abstract: Introduction: Persistent sciatic artery (PSA) is a rare embryological vascular anomaly with a prevalence between 0.025–0.06%. PSA is frequently associated with aneurysmal degeneration and can result in neuropathy, thrombosis, or rupture, threatening limb and life. Case presentation: We present a case of a 72-year-old man with an incidental finding of a right sided 4 cm PSA aneurysm with limited symptoms. The aneurysm was treated successfully with endovascular exclusion and a femoral-popliteal bypass was performed to revascularize the leg. Discussion: Treatment of PSA aneurysms involve excluding the aneurysm and revascularizing the involved leg. Improvements in endovascular embolization techniques now offer new solutions in the management of these aneurysms. Conclusion: A high degree of clinical suspicion is required to properly diagnose and treat PSA aneurysms. Referral to a center with expertise in both open and endovascular techniques is vital to ensure good outcomes.